Sejarah Religio-Politik di Singapura: Interaksi Islam dalam Dinamika politik Multi Etnis - Mustofa Umar (Millah: Journal of Religious Studies, 2004)
In this article, the writer tries to explain the historicity of political system formulation and government in Singapore. Besides, the writer also explores the religion role in establishing state institution. Moreover, the writer specifies that social structure of Singapore society-the multiracial country with the majority of Chinese immigrant have been working out nationalism awareness. The political social interaction based on ethnic and religious sentiment had crystallized and ended by separation of Singapore from Malaysia federation, as a free country based on industry and trade. In many sectors, the sake of Singaporean Moslems is accommodated. The accommodated Moslems' aspiration is along with the improvement of Moslems awareness of the important of formal institution to accommodate their aspiration. However, Islam is still paced as a distrustful movement.